Technical, economical, and socio-environmental analysis of forest road maintenance using the HDM-4 software - Breno Santos Arrivabeni; Carlos Cardoso Machado; Raiane Ribeiro Machado Gomes; Ana Paula Mendes Teixeira (Transportes, 2023)
As they do not have a sealant coating, forest roads are more susceptible to degradation and traffic obstruction, requiring better construction and maintenance attention. This study aimed to assess the performance of maintenance carried out on unpaved roads in technical, economic, and socio-environmental scopes by application of the Highway Development & Management Model (HDM-4) and to show the best project proposals. The analyses consisted of inputting the HDM-4 with the characteristic data of roads, of and the maintenance to be adopted and the type of used vehicle. The association of this information made it possible to envision scenarios that consider either the replacement or non-replacement of gravel materials on the roads as a methodology. For management without gravel replacement, the most effective scenario was that of roads with gravel under the bed, located in a tropical climate, with flat features and 90 kilometers in length, initial thickness of 175 mm of gravel, high volume of traffic, and subject high-level maintenance at 30-day intervals. For the management with gravel replacement, the ideal scenario was that of roads with gravel under the bed, located in a temperate climate, on rolling terrain and 30 kilometers long, initial thickness of 175 mm of gravel, high traffic intensity, and subjected to high-level maintenance every 30 days. High-level maintenance was the best option for maximizing the quality of the roads and providing the best total net benefit, lowest gas emission rates, least fuel, and tire consumption, and adequate pavement condition by the end of the project.